Bacteriophages and Lysins as Possible Alternatives to Treat Antibiotic-Resistant Urinary Tract Infections - Trinidad de Miguel; José Luis R. Rama; Carmen Sieiro; Sandra Sánchez; Tomas G. Villa (MDPI AG, 2020)
Urinary tract infections represent a major public health problem as the rapid emergence of antibiotic-resistant strains among uropathogens is causing the failure of many current treatments. The use of bacteriophages (phages) and their derivatives to combat infectious diseases is an old approach that has been forgotten by the West for a long time, mostly due to the discovery and great success of antibiotics. In the present so-called "post-antibiotic era", many researchers are turning their attention to the re-discovered phage therapy, as an effective alternative to antibiotics. Phage therapy includes the use of natural or engineered phages, as well as their purified lytic enzymes to destroy pathogenic strains. Many in vitro and in vivo studies have been conducted, and these have proved the great potential for this therapy against uropathogenic bacteria. Nevertheless, to date, the lack of appropriate clinical trials has hindered its widespread clinic application.